Potentials of cemetries as urban tree conservation areas in Ibadan metropolis (2015)
A cemetery, because of its presumed sanctity, is less disturbed from other land use activities in the urban areas and thus serves in many cases as the last remnant for greenery and conservation of trees in many large cities. However, there is little information on the population, diversity and management of trees in cemeteries located in the Ibadan metropolis. Therefore, this study was carried out to determine the potentials of cemeteries as urban tree conservation areas. Eight cemeteries under different management within the metropolis were sampled and their tree species composition, density and population determined. Their land areas were also determined and the trees, classified based on their origin and uses. The size of the cemeteries ranged from 0.03 - 0.48 km2. There were 48 tree species from 22 different families represented in the eight cemeteries, with 28 of these species indigenous to the lowland rainforest ecosystem. Fabaceae family had the highest species representation. Cemeteries under government and institutional management had a larger representation of trees than the private and religious ones, with the highest number of trees (399) found in the Ibadan South East Cemetery, Orita-Aperin which had a tree density of 0.014 m-2. The University of Ibadan cemetery recorded the highest species composition (28) with a tree density of 0.03 m-2. Albizia zygia had the highest number of identified uses (15), while shade and shelter were the most common attributes of trees in the cemeteries. They could assist in the preservation of tree genetic diversity and serve as botanic refuge for many threatened species. Therefore, management of modern city cemeteries require enlightenment on the conservation role such facilities could play in urban areas.